Pengaruh Inisiatif Terhadap Kinerja Pegawai Pada Kantor Camat Koto Tangah Kota Padang - F. Yasmeardi Yasmeardi; Dian Rizke; Niko Fernando (Jurnal Public Administration, Business and Rural Development Planning, 2019)
This research is aimed (1) to find out the level of Employees’ Initiatives and performance at the Koto Tangah District Office in Padang, (2) to determine the effect of the Initiative on Employee Performance at the Koto Tangah District Office in Padang.This research uses the Initiative quantitative method as an independent variable and Employee Performance as the dependent variable. The sample in this study were all employees working at the Koto Tangah District Office in Padang. The statistical method uses simple analysis, by testing the t-test hypothesis.From the results of this study the following conclusions are obtained: 1). Level of Employee Initiative in the Padang Koto Tangah District Office based on the results of a questionnaire that researchers distributed at the Padang Koto Tangah District Office, the average score of Initiative Variables was 12.1 with a Total Initiative Respondent Achievement (TCR) of 75.32% at 61% -80 % with Good criteria. This means that the Respondent gave a Good rating from the Initiative, 2). Level of Employee Performance in the Padang Koto Tangah District Office based on the results of a questionnaire that researchers distributed at the Padang Koto Tangah District Office, the average Employee Performance Variable score was 7.73 with a Total Respondents Achievement (TCR) of 77.25% at 61% - 80% with Good criteria which means the respondent gives a good Employee Performance rating, 3). There is a positive effect of the Initiative Variable on the Employee Performance Variable in the Koto Tangah District Head Office.